2012
DOI: 10.1139/w2012-101
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of TerD-domain-encoding genes: effect on Streptomyces coelicolor development

Abstract: TerD-domain-encoding genes (tdd genes) are highly represented in the Streptomyces coelicolor genome. One of these, the tdd8 gene, was recently shown to have a crucial influence on growth, differentiation, and spore development of this filamentous bacterium. The investigation of the potential role of tdd genes has been extended here to tdd7 (SCO2367) and tdd13 (SCO4277). Both genes are highly expressed in bacteria grown in liquid-rich medium (tryptic soy broth). However, the deletion of these genes in S. coel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It is noteworthy that the TerD-like protein SCO2368, a protein known to down-regulate the expression of genes of the DosR-like regulon, was more abundant in S. lividans than in S. coelicolor . The function of the other TerD proteins is not clearly known, but some studies suggest that these proteins might play a role in growth slowdown under adverse conditions to improve cell survival. , In addition, a proteomics study of S. viridochromogenes showed the up-regulation of tellurium resistance proteins in response to oxidative stress . A protein of the universal stress protein (USP) family (SCO7299) was also found to be 5.7 times more abundant in S. lividans than in S. coelicolor .…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the TerD-like protein SCO2368, a protein known to down-regulate the expression of genes of the DosR-like regulon, was more abundant in S. lividans than in S. coelicolor . The function of the other TerD proteins is not clearly known, but some studies suggest that these proteins might play a role in growth slowdown under adverse conditions to improve cell survival. , In addition, a proteomics study of S. viridochromogenes showed the up-regulation of tellurium resistance proteins in response to oxidative stress . A protein of the universal stress protein (USP) family (SCO7299) was also found to be 5.7 times more abundant in S. lividans than in S. coelicolor .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it was demonstrated that deletion or overexpression of tdd7, tdd8, or tdd13 affected morphological differentiation or spore production in S. coelicolor (11,13). A strain with a deletion in tdd8 (SCO2368) produced long chains of short spores with a dense spore wall, while a strain overexpressing tdd8 produced very few spores of irregular shapes and sizes (11).…”
mentioning
confidence: 99%